Índices urbanísticos e o ambiente térmico: estudo em uma fração da cidade de São Carlos -SP - Vasconcelos, Juliano Souza (2014)
Though urban form affects the thermal environment, there are only a few legal tools that include the thermal issue in the city planning and urban design. This research established a link between urban form and thermal environment, by considering urban indexes such as the occupation coefficient, the floor space index and the vegetation cover index, to characterize the land use and occupation. For this purpose, the study area was an urban fraction of the Brazilian city of São Carlos, in State of São Paulo. Several points of the study area were taken as references for thermal measurements, while others regional data of the climate were registered by the meteorological station situated in the city skirts. The data were collected in periods representing dry weather of winter months. The measurements allowed the validation of a computational model applied for microclimatic simulation of the urban area - the ENVI-met. The best situation performed by the model was determined by comparison of real and simulated data. This process allowed data extraction by simulation of the whole area and the development of thermal maps, considering the real urban situation, a scenario of densification and a scenario of green areas. The results pointed out that the rise of the occupation coefficient causes a slight elevation of the air temperature. Even more significant tendencies were also assessed by the development of a multiple regression model, revealing the potential of the floor space index, the urban green cover and their association with the wind speed.